Acute idiopathic pulmonary hemorrhage in infants. Report of two cases and literature review (2016)
Acute idiopathic pulmonary hemorrhage is a rare life-threatening disease in children. The classic triad includes hemoptysis, anemia and respiratory distress. Since clinical presentation may vary, diagnosis can be difficult. Severe respiratory distress, and ventilatory failure requiring mechanical ventilation are often present. Chest X-rays usually show unilateral or bilateral infiltrates, therefore, other causes of pulmonary hemorrhage must be excluded, since most of them correspond to systemic diseases. Treatment often requires intravenous steroids to solve the respiratory failure in most cases. We present two cases involving infants treated at Hospital San José (a fourth level hospital in Bogotá, Colombia) with acute idiopathic pulmonary hemorrhage which required mechanical ventilation and responded to intravenous steroids. A literature review was conducted with special emphasis on clinical presentation, diagnosis and therapeutic approaches.